EVALUASI PENYAJIAN DAN PENGUNGKAPAN ASET TETAP BERDASARKAN PSAK NO. 16 PADA PT. AKAM - Hukom, Hosianita Fiandani; Morasa, Jenny; Pangerapan, Sonny (Universitas Sam Ratulangi, 2018)
A prime company entity can be seen through the companyâ€™s financial statement that is based on Financial Accounting Standards as a guidance in producing the financial statement. Fixed assets is a supporting element which has a quite large value and an important position in a company, therefore the information about the asset should comply with the prevailing standards. The aim of this research is to find out whether the presentment and disclosure of regular assets at PT. AKAM are in conformity with the Statement of Financial Accounting Standards (SFAS) No. 16 concerning property and equipment. The writer uses descriptive method, and the data collection was through interview, observation, and documentation. PT. AKAM is a company entity that engaged in construction service. According to the research result, it can be concluded that the presentment and disclosure of company fixed assets have led to Statement of Financial Accounting Standards (SFAS) No.16.Â Keywords : Presentment, Disclosure, Fixed Asset, SFAS 16.